Retrospective analysis of ultrasound criteria for newly diagnosed extragenital endometriosis detected during preventive examinations - O. E. Nechaeva; I. S. Gruzdev; Yu. V. Popov; A. G. Kedrova; V. N. Lesnyak; N. S. Nosenko (ABV-press, 2020)
Endometriosis is a common pathological condition characterized by the presence of endometrial glands and stroma outside the uterus, most frequently in the pelvis. Despite the ability to demonstrate infiltrative growth and tendency to local recurrence and invasion, endometriosis is considered as a benign proliferative disease. An increasing incidence of extragenital endometriosis (including that in young patients) and difficulties associated with its visualization during ultrasonography lead to a delayed diagnosis, resulting in an increase in the number of cases of advanced endometriosis, which requires long-term treatment. The improvement of a screening ultrasound tomography technique and development of specific ultrasound criteria for preventive examination will ensure rapid identification of patients requiring treatment. In this retrospective study, we analyzed 57 cases of extragenital endometriosis detected during preventive examinations of women between 2014 and 2019. Each case was analyzed with the consideration of ultrasound characteristics together with clinical and gynecological data. We evaluated location, size, contours, and structure of foci. We propose a method of extended ultrasound examination in women with suspected extragenital endometriosis.